How Do We Treat Children with Anterior Cutaneous Nerve Entrapment Syndrome and Is the Biopsychosocial Model Also Being Applied? A Scoping Review - Anke P. C. Top; Thomas G. de Leeuw; Wichor M. Bramer; Bernadette C. M. de Mol; Frank J. P. M. Huygen; Maaike Dirckx (Pain Research and Management)
Background. Evidence-based guidelines for managing anterior cutaneous nerve entrapment syndrome (ACNES) in children are absent. The primary aim of this review was to scrutinize the evidence supporting currently used treatment interventions. In accordance with the World Health Organization (WHO) guidelines for managing chronic pain in children, these patients and their families and caregivers should be treated within the context of the biopsychosocial model; pain should not be treated purely as a biomedical problem. Therefore, our second aim was to evaluate whether these interventions are applied within the context of the biopsychosocial model, utilizing an inter- or multidisciplinary approach. Materials and Methods. A scoping review of the literature was conducted to explore treatment strategies for ACNES in children. To ensure a comprehensive overview of published literature on this topic, the search was not restricted based on study type. Two reviewers independently assessed titles and abstracts. After excluding records unrelated to children, full texts were screened for inclusion. Any discrepancies in judgement were resolved through discussion with a third reviewer. Results. Out of 35 relevant titles, 22 were included in this review. Only 4 articles provided information on long-term outcomes. The overall quality of the review was deemed low. The majority of reports did not address treatment or education within the psychological and social domains. A structural qualitative analysis was not feasible due to the substantial heterogeneity of the data. Conclusion. The evidence supporting current treatment strategies in children with ACNES is of low quality. More research is needed to establish an evidence-based treatment algorithm for patients with this challenging pain problem. In line with the WHO recommendation, greater emphasis should be placed on a biopsychosocial approach. The ultimate goal should be the development of a generic treatment algorithm outlining an approach to ACNES applicable to all professionals involved.